Exploring power shifts as an enabler for a strengthened patient role in quality improvements: a Swedish survey study. Issue 1 (1st March 2021) - Gremyr, Ida; Elg, Mattias; Eriksson, Erik; Halldórsson, Árni; Smith, Frida; Gustavsson, Susanne
Abstract : Objectives: This study examined the relationship between professionals' perceptions of a strengthened role for the patient and of patient involvement in quality improvement (QI) and whether professionals' experiences in improvement science were a moderator on such a relationship. Design: From a predominantly close-ended, 44-item questionnaire, 4 questions specifically concerning professionals′ perception on patient involvement in QI were analysed. Setting: Three Swedish regions. Participants: 155 healthcare professionals who had previously participated in courses in improvement science. Results: The covariate patient involvement was significantly related to a perceived strengthened patient role. There was also a significant interaction effect between degree of patient involvement and professionals' experience in the area of improvement science on a strengthened patient role. The result shows that there is a relationship between the perceived level of patient involvement in improvements and professionals' perceptions of a strengthened patient role. In this study, the covariate, perceived patient involvement, was significantly related to experiences of more equal relationships between patients and healthcare professionals. There was also a significant interaction effect between the degree of patient involvement and professionals' experience in the area of improvement science, for a more equal relationship between patients and healthcare professionals. Conclusion: Increased patient involvement in QI is a means of strengthening the patient role and supporting a more equal relation between patients and healthcare professionals. Furthermore, empirical evidence shows that the healthcare professionals' experiences in the area of improvement science support a strengthened patient role and a more equal power relationship, but for this to happen, the mindset of professionals is key. Future research is needed to capture and investigate the experiences from patients and relatives about being involved in QI in healthcare, and to study the effects on quality in care processes.